Possibilities of boron neutron capture therapy in the treatment of malignant brain tumors - V. V. Kanygin; A. I. Kichigin; N. V. Gubanova; S. Yu Taskaev (Вестник рентгенологии и радиологии)
Boron neutron capture therapy (BNCT) that is of the highest attractiveness due to its selective action directly on malignant tumor cells is a promising approach to treating cancers. Clinical interest in BNCT focuses in neuro-oncology on therapy for gliomas, glioblastoma in particular, and BNCT may be used in brain metastatic involvement. This needs an epithermal neutron source that complies with the requirements for BNCT, as wellas a 10B-containing agent that will selectively accumulate in tumor tissue. The introduction of BNCT into clinical practice to treat patients with glial tumors will be able to enhance therapeutic efficiency.